Hybrid controller for swinging up and stabilizing the inverted pendulum on cart - Asa, Ekachai; Benjanarasuth, Taworn; Ngamwiwit, Jongkol; Komine, Noriyuki (My University, 2008)
In this paper, a hybrid controller for swinging up and stabilizing an inverted pendulum on cart is presented. The energy control concept is employed to swing the inverted pendulum up to around the upright position within the assigned switching condition. After that, the stabilizing controller is then switched to stabilize the inverted pendulum at the upright position. The stabilizing controller is a linear servo state feedback controller designed by Coefficient Diagram Method. The simulation results show that the designed hybrid controller can be mutually operated with acceptable efficiency.
Keywords: Coefficient diagram method (CDM); Energy control method; Inverted pendulum